EFEKTIVITAS KOLABORASI FARMASI DAN KEPERAWATAN DALAM MENINGKATKAN KEPATUHAN PENGOBATAN OSTEOPOROSIS: SEBUAH TINJAUAN SISTEMATIK - Ismedsyah; DIna Indarsita (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2026)
Background: Osteoporosis is a common bone disease in the elderly population, which can lead to an increased risk of fracture and a decreased quality of life. Adherence to osteoporosis medication is crucial for improving treatment effectiveness and preventing fractures. Objective: This systematic review aims to evaluate the effectiveness of pharmacy and nursing collaboration in improving adherence to osteoporosis medication.